2020
DOI: 10.1111/apt.15673
|View full text |Cite
|
Sign up to set email alerts
|

Modelling NAFLD disease burden in four Asian regions—2019‐2030

Abstract: Summary Background Non‐alcoholic fatty liver disease (NAFLD) and non‐alcoholic steatohepatitis (NASH) account for an increasing proportion of liver disease in the Asia‐Pacific region. Many areas in the region are experiencing epidemics of metabolic syndrome among rapidly ageing populations. Aims To estimate using modelling the growth in NAFLD populations, including cases with significant fibrosis that are most likely to experience advanced liver disease and related mortality. Methods A disease progression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
112
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 48 publications
0
112
0
2
Order By: Relevance
“…19 Importantly, the disease and economic burden of NAFLD will probably increase during the coming decades. 20,21 Health-care utilisation and expenditure are particularly high among patients with NAFLD and advanced fibrosis or type 2 diabetes and those requiring hospital admis sion. 22,23 Little information is available regarding the effect of NAFLD on patients' daily lives, 24 which will be important data to collect in future intervention or treatment studies.…”
Section: Epidemiology and Disease Burdenmentioning
confidence: 99%
“…19 Importantly, the disease and economic burden of NAFLD will probably increase during the coming decades. 20,21 Health-care utilisation and expenditure are particularly high among patients with NAFLD and advanced fibrosis or type 2 diabetes and those requiring hospital admis sion. 22,23 Little information is available regarding the effect of NAFLD on patients' daily lives, 24 which will be important data to collect in future intervention or treatment studies.…”
Section: Epidemiology and Disease Burdenmentioning
confidence: 99%
“…Interestingly, MAFLD impacts children’s health in an asymptomatic profile that is incidentally diagnosed at a mean age of 11–13 years [ 21 , 22 , 23 ]. Overall, MAFLD mortality is escalating [ 24 ] with an estimated rise between 65% and 100% from 2019 to 2030 in the Asia-Pacific region alone [ 25 ], as well as the US, China, and France, which is combined with an alarming MAFLD predicted prevalence escalation to occur in Germany, Italy and the UK by 2030 [ 26 ].…”
Section: From Nafld To Mafld—what Is Going On?mentioning
confidence: 99%
“…Non‐alcoholic fatty liver disease (NAFLD) causes significant economic burden 1 and impairment of health‐related quality of life 2 . Estes et al reported the projected burden of non‐alcoholic liver disease (NAFLD) based on Markov modelling in four developed Asian countries during 2019‐2030 3 . Over the 12‐year period, prevalent NAFLD cases would increase between 6% and 20%, while prevalent non‐alcoholic steatohepatitis cases would increase between 20% and 35%.…”
Section: Easta Westbmentioning
confidence: 99%